(untitled) (Journal of Oriental Studies, 2019)
This article analyzes the importance of the Caspian Sea in the region. Until recently, although the Caspian Sea and the Caspian Sea region were taken into account in geopolitical and strategic layouts, it was not enough clearly. It was believed that the Caspian Sea is a closed inland body of water that has no connection with the oceans, and in the balance of forces in its basin has been changed. They also considered the development of discussions and negotiations in order to determine the status of the Caspian Sea, and the share of each country in the Caspian region. This article analyzes the relations between the countries of the Caspian region, since in this region the interests of many states intersect, not only located in this region, but also many thousands of kilometers away. The military-political situation taking shape here, the proximity of areas of unresolved conflicts, manifestations of terrorist activity, drug trafficking and illegal migration, determine its strategic importance. The article is based on the use of the interdisciplinary nature of the subject and on the works of Kazakh and foreign authors. Key words: Caspian Sea, Features of the Caspian Sea, Geographical factors in the Caspian Sea, strategic factors in the Caspian Sea.